Estudio geológico estructural de la galería de exploración avanzada en la concesión minera “Chapadero G” (código 600009.1) ubicado en el cantón Paltas provincia de Loja. - Silverio Ludeña, Juan Pablo (2016)
The present investigation refers to the "Geological Structural Study of the Gallery of Advanced Exploration in the Mining Concession "Chapadero G" (code 600009.1) which is located in the Canton of Paltas, province of Loja", covering an area of 200-hectare adjacent mining, of which the study was based on 14 hectares that correspond to the zone of current exploration. A total station S6, GPS and a meter were used to obtain detailed results in a superficial topographic uprising in an area of 14.06 hectares which corresponds to the zone of exploration in a scale of 1:2000 and the subterranean uprising in a scale of 1:500; which allowed us to obtain the real topography of the superficial are as well as the interior mines. Once we obtained the superficial and subterranean topographic base a map was designed which represents the superficial geology. This thesis will also describe the most important outcrops, geo-referencing them and taking samples for its petrographic analysis which established the geology of the sector and led to determine that this sector is located in the intruder one of the Batholith Tangula, specifically composed by granodiorite stone, greenstone and some dykes of basaltic andesite. In order to do the geological structural upraising of the gallery, a measurement of the structural elements found inside the gallery was done, which concluded in several mineralized veins with a direction from 245 ° to 268 ° with dips between 64 ° to 88 ° SE, also dikes and intrusions of limonite were found. Three zones were considered to identify their geological features and structural domains in the Geomechanics Classification of the gallery, applying the Rock Mass Rating (RMR) established by Bieniawski. Here, in an area of 1m x 1m it was possible to identify such parameters such as: index of Rock Quality Designation (RQD), a space between discontinuities, water infiltration condition and discontinuities orientation. Also, a rock sample was taken for the analysis of its uniaxial resistance. Therefore, a numerical value was obtained which allowed us to classify the mass rock and to propose recommendations for its possible sustenance.